(untitled) (Pulse, 2024)
Background: The Rhesus (Rh) blood group is the most immunogenic blood group in humans among all blood groups. It is one of the complex systems in immunohematology containing 56 different antigens. The Rh blood group shows variable expression of D antigen due to gene polymorphism. The variable expressions are weak D, partial D, and DEL. Materials and Methods: A retrospective observational study was conducted at Evercare Hospital Chattogram from April 2021 to March 2023. Blood samples obtained for ABO and RhD blood grouping were tested by column agglutination technique. RhD negative samples were further tested for Du testing to identify weak-D phenotype. Results: A total of 5700 blood samples were taken from patients. Out of these 5496 (96.5%) were RhD positive while 204 (3.5%) were RhD negative. Among Rh D negative cases, 4 were weak-D positive constituting 1.9% among Rh D negatives and 0.07% among total patients. Conclusion: All RhD negative samples should be checked for Du testing. We must take caution on application of the Du test. It may be used to decrease the burden of RhD negative transfusion. Pulse Vol.15, 2023 P: 38-40